PENGARUH ENDORSEMENT DAN PERSONAL BRANDING TERHADAP KEPUTUSAN PEMBELIAN PRODUK UMKM KULINER DI WILAYAH SIMPANG IV SIPIN, KECAMATAN TELANAIPURA KOTA JAMBI - Rahma Alia; Maulana Yusuf; Hareastoma Hareastoma (Nusantara Hasana Journal, 2026)
This study aims to analyze the influence of endorsement and personal branding on purchasing decisions for culinary MSMEs products in Simpang IV Sipin Village, Telanaipura District, Jambi City, both partially and simultaneously. The research is grounded in the phenomenon that culinary MSMEs increasingly rely on influencer endorsement and the personal branding of business owners in digital marketing, yet not all MSME applying these strategies experience a significant increase in sales, alongside inconsistencies found in previous studies. This research employs a quantitative associative-causal approach using multiple linear regression analysis. The sample consisted of 96 consumer respondents aged 18–35 years, selected through purposive sampling, with criteria of having purchased culinary MSME products at the research location and having been exposed to endorsement promotions on social media. The results yield the regression equation Y = 21.349 + 0.488X₁ + 0.225X₂. Partially, endorsement has a positive and significant effect on purchasing decisions (t-value 3.364 > t-table 1.986; sig. 0.001 < 0.05), while personal branding has a positive but not significant effect (t-value 1.539 < t-table 1.986; sig. 0.091 > 0.05). Simultaneously, both variables have a positive and significant effect on purchasing decisions (F-value 11.904 > F-table 3.094; sig. 0.001 < 0.05), with an Adjusted R Square of 0.187, or 18.7%. These findings indicate that endorsement is a more dominant factor than personal branding in driving culinary MSMEs consumers' purchasing decisions.